A reflection on a peripheral movement; The “Save Aru” social movement 2013-2015 from a historical perspective - Sahrasad, Herdi; Chaidar, Al; Syam, Maksum (Wacana, Journal of the Humanities of Indonesia, 2022)
This article examines the struggle of the Aru Islands community to preserve their forests and their natural environment in the shape of the “Save Aru” social movement from 2013 to 2015. Today this social movement is still alive and kicking. In 2010, the Aru Islands community was taken by surprise by the plan of a private corporation (PT Menara Group or PT MG) to annex forest areas in the Aru Islands in order to convert them into sugar-cane plantations. Their outrage at this plan spurred the citizens of Aru to fight the might of this corporate and preserve their forests and environment. Not all has gone smoothly as the civil society movement in Aru has been divided into pro-splitting and counter-splitting on a regional division agenda. Meanwhile, this exploitative business has become a scourge for the Aru people who want to preserve their forests and the environment as a whole. Thanks to the campaign, environmental awareness appears to be growing rather than abating among the Aru Islands community. Young people in the Aru have been sharing their stories about the natural resources around them under threat from the power of private corporate capital with friends, family, and neighbours. The danger of deforestation by private corporations is a problem and a challenge that must be faced by all communities, whether they be Aru, Indonesian, or international, who care about the preservation of the forests in the Aru Islands as a “lung” of the world, helping to reduce the effects of global warming and the ozone depletion.